2017
DOI: 10.1371/journal.pone.0180474
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of soluble forms of E-selectin and ICAM-1 adhesion molecules during human leptospirosis

Abstract: Leptospirosis is a multisystemic zoonotic disease with infiltration of visceral organs by Leptospira. The capacity of the vascular endothelium to grant immune cell recruitment and activation in target organs during the disease course remains poorly characterized. We ascertained the levels of expression of several soluble cell adhesion molecules (CAM) notably expressed by endothelial cells in human leptospirosis. We prospectively enrolled 20 hospitalized patients and compared them to 10 healthy controls. Diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
7
2
Order By: Relevance
“…This leads to a combined increase in E-selectin of approximately 19% versus placebo in rest. Similar to what we describe for P-selectin, absolute baseline values of E-selectin are much smaller than reported previously for healthy volunteers (from 27800 to 54000 pg/mL in a review (Roldan et al 2003) to 314000 pg/ mL in one other study (Raffray et al 2017)). This review describes significant differences between cases and controls, with increases in E-selectin of 30-50% for diabetes and hypertension.…”
Section: Effects On E-selectinsupporting
confidence: 84%
“…This leads to a combined increase in E-selectin of approximately 19% versus placebo in rest. Similar to what we describe for P-selectin, absolute baseline values of E-selectin are much smaller than reported previously for healthy volunteers (from 27800 to 54000 pg/mL in a review (Roldan et al 2003) to 314000 pg/ mL in one other study (Raffray et al 2017)). This review describes significant differences between cases and controls, with increases in E-selectin of 30-50% for diabetes and hypertension.…”
Section: Effects On E-selectinsupporting
confidence: 84%
“…Soluble forms of the adhesion molecules such as VCAM-1 and ICAM-1 can be detected in plasma and are a good indicator of their availability on the cell membrane (Raffray et al. 2017). Also, in preclinical practice and experimental studies, one surrogate marker to detect atherosclerosis is the measurement of blood vessel IMT (Stein et al.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte aggregation along the vascular wall of lesion regions is a prerequisite for the adherence of WBC and endothelial cells and passing through blood vessel wall ( 21 ). ICAM-1 is an adhesion molecule with a very small molecular weight that promotes leukocyte adhesion and aggravates inflammatory damage ( 22 ). Studies have shown that ICAM-1 and E-selectin are increased in sepsis peripheral blood, and the content of those two factors in serum can be used to judge the extent of endothelial damage.…”
Section: Discussionmentioning
confidence: 99%